Outcomes from a One-Week Adapted Sport and Adapted Adventure Recovery Programme for Military Personnel - Peacock, Suzanne M. (Sports (Basel), 2019)
Background: The Battle Back Centre offers a bespoke, Self Determination Theory-oriented adapted sport and adventurous training programme centred on experiential learning and reflection to support the recovery of military personnel. Aim: To identify the short-term impact of participation in the programme on positive mental health and psychological need satisfaction. Method: Participants were 978 wounded, injured and sick (WIS) personnel classified as: Wounded (battle casualties), Injured (non-battle casualties) and Sick (mental/physical illness). Participants completed the Basic Need Satisfaction in General Scale (Gagné, 2003) and Warwick and Edinburgh Mental Well Being Scale (Tennant et al. 2006) on arrival and course completion. Results: All measures of positive mental health and psychological need satisfaction showed statistically significant increases, with a large effect size, from baseline to course completion (mean ± SD change in positive mental health, competence, autonomy and relatedness were 7.19 ± 9.61, 0.46 ± 0.9, 0.27 ± 0.84, 0.26 ± 0.86, respectively, p < 0.05). While the average magnitude of the intervention effect for positive mental health (16%) is comparable or greater than other reported interventions, changes were achieved in a shorter time. Conclusion: Findings highlight the positive short-term effect adapted sport and adventurous activities have for WIS personnel. Declaration of interest: Work supported by The Royal British Legion.